Contact resistance stability and cation mixing in a Vulcan-based LiNi1/3Co1/3Mn1/3O2 slurry for semi-solid flow batteries. Issue 19 (28th April 2021) - Jacas Biendicho, Jordi; Hemesh, Avireddy; Izquierdo, Victor; Flox, Cristina; Morante, Joan Ramon
Abstract : Electrical contact resistance and cation mixing have been identified as physico-chemical factors limiting the performance of semi-solid flow batteries. Abstract : The Semi-Solid Flow Battery (SSFB) is an interesting energy storage system (ESS) for stationary applications but, in spite of the significant work presented on this technology so far, understanding the chemical and physical factors limiting its electrochemical performance is still blurred by measurements under static conditions rather than under real operando conditions. In this study, we have used Vulcan carbon as a conductive additive to formulate LiNi1/3 Co1/3 Mn1/3 O2 (NCM) based slurries as the catholyte to characterize electrical and electrochemical performances using a 3-electrode flow cell by electrochemical impedance spectroscopy (EIS) and galvanostatic charge/discharge (GCD), respectively. The results are correlated with post-mortem analyses of recovered slurries using Scanning Electron Microscopy (SEM), Raman spectroscopy and Rietveld refinement of the NCM crystal structure. Due to the improved electrochemical cycling stability of the Vulcan-based NCM slurry and cell configuration used for measurements, we have been able to characterize the system in terms of electrical contributions and correlate them with particle degradation as well as detect antisite defect formation on cycling. The electrical stability of the contact resistance and cation mixing are identified as factors limiting the performance of the semi-solid slurry. The latter is frequently reported in porous electrodes for Li-ion batteries but, to our knowledge, it has not been reported for SSFBs to date.